Late left atrial appendage closure device displacement and massive thrombus formation: a case report. Issue 2 (20th February 2020) - Sasko, Benjamin; Ritter, Oliver; Bramlage, Peter; Riediger, Fabian
Abstract: Background : Left atrial appendage (LAA) closure with the WATCHMAN device is an alternative to anticoagulation therapy for the prevention of stroke in selected patients with atrial fibrillation (AF). Infrequently, left atrial (LA) device-related thrombus formation occurs and it is poorly understood. Thrombus formation due to incomplete covering of the LAA is even rarer and may occur within the first few months after device implantation. Case summary : Here, we present a case of a 68-year-old male patient with permanent AF, drug- and hepatitis induced liver cirrhosis (CILD Score B), and prior aortic valve replacement. The patient had a history of percutaneous LAA closure using a WATCHMAN device. He developed massive peri-device leak and thrombus arising from the space between the device and appendage cleft 2 years after implantation. Because of the high bleeding risk with a HAS-BLED score of 5 points, surgery was chosen as the therapy of choice instead of long-term anticoagulation. The patient was discharged in good clinical condition and has been scheduled for a yearly follow-up. Discussion : This case emphasizes the importance of choosing appropriately sized LAA occluder devices and planning for regular post-interventional follow-ups to minimize the risk of per-device leaks and thrombi.